2003
DOI: 10.1590/s1413-70542003000200018
|View full text |Cite
|
Sign up to set email alerts
|

Atividade de alguns insetos em flores de Brassica napus L. em Dourados-MS e a interação com fatores climáticos

Abstract: RESUMO Objetivou-se estudar a flutuação populacional, horários de visitação e a interação com fatores climáticos de insetos visitantes de flores de Brassica napus L. em diversos estádios fenológicos. O trabalho foi realizado em Dourados, MS, Brasil. Os insetos foram coletados com rede entomológica de 30 cm de diâ-metro, a cada duas horas, no período de 7 as 17 horas. Foram coletadas as abelhas Apis mellifera, Linnaeus, 1758, Trigona sp., o vespídeo Brachygastra lecheguana (Latreille -1824) e uma espécie de Chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 6 publications
(2 reference statements)
1
10
0
1
Order By: Relevance
“…Insects therefore have important roles in the reproduction of C. abyssinica and can maximize productivity by increasing fruit and seed production and improving their quality -a situation that has been observed in other economically valuable cultures such as Brassica napus L. (Mussury and Fernandes 2000, Mussury et al 2003, Jauker and Wolters 2008 and Raphanus sativus L. (Teixeira and Zampierom 2007).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Insects therefore have important roles in the reproduction of C. abyssinica and can maximize productivity by increasing fruit and seed production and improving their quality -a situation that has been observed in other economically valuable cultures such as Brassica napus L. (Mussury and Fernandes 2000, Mussury et al 2003, Jauker and Wolters 2008 and Raphanus sativus L. (Teixeira and Zampierom 2007).…”
Section: Resultsmentioning
confidence: 97%
“…Rosa et al (2011) likewise concluded that these same bees were the most frequent pollinators of rapeseed, and recommended introducing colonies of these insects to increase seed production. In their study of B. napus, Mussury et al (2003) pollinators was between 09:00 and 15:00. Williams (1985) observed that most bee activity on B. napus occurred between 06:30 and 15:00, with most of the pollen being collected between 08:00 and 10:00 -probably because of the more favorable temperature and relative humidity at that time of day.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Neste caso, a diversifi cação teria o potencial de oferecer locais para nidifi cação ou áreas de refúgio, sem prejudicar a interação predador-presa. Alternativamente, o aumento na taxa de predação pode estar relacionado com (1) a atração de vespas em busca de presas alternativas (Reis & Souza 1983) e/ou (2) o acesso a recursos como pólen e néctar, observado em indivíduos da família Vespidae (Maingay et al 1991, Giannotti et al 1995, Mussury et al 2003.…”
Section: Discussionunclassified